PENINGKATAN DISOLUSI NIFEDIPIN DENGAN PELARUT PVP K-30 MENGGUNAKAN METODE DISPERSI PADAT - Asri Prahmanita Sadiarti; Endang Diyah Ikasari; A.Ariani Hesti W.S (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2022)
Nifedipine is an anti-hypertensive included in the Biopharmaceutics Classification System (BCS) class II to its nature of being poorly soluble in water, resulting in low bioavailability. One technique that can be used to improve the solubility of the dispersion technique. This research aimed to determine the effect of the concentration of PVP K-30 on physical characteristics, the dissolution rate of solid dispersions, and the interactions that occur between nifedipine with PVP K-30. The method of manufacturing solid dispersion is a melting-solvent method. FI - F III is a solid dispersion and F IV-VI F is a physical mixture. Formula used is the ratio of nifedipine: PVP K-30 FI (10%: 90%), F II (20%: 80%), F III (30%: 70%), F IV (10%: 90%), FV (20%: 80%), F VI (30%: 70%), and used as a control of pure nifedipine. Testing was conducted on the organoleptic test, flow rate, moisture content, melting point, dissolution testing, and FT-IR analysis. Dissolution test parameters used C (20). The data was obtained and analyzed by non-parametric test KruskalWallis and Mann-Whitney with a level of 95%. The results showed that solid dispersions aregranulated, yellow, and have a free-flowing nature. Test results C (20) FI, F II, F III, F IV, FV, F VI, and controls respectively were 89,48%; 51,75%; 22,58%; 12,88%; 24,07%; 26,34%; 24,95%. The results showed that the FI has the highest dissolved. Results of FT-IR spectra showed no interaction between nifedipine with PVP K-30.